Penny Postcard of E.P. Foster Library - United States Post Office::::::
Penny postcard image of the E.P. Foster Public Library in Ventura, CA, as it stood from 1921 to 1959, when new construction extended the library over the lawn to Main Street. Image digitized by Broome Library, California State University Channel Islands. Original 35mm slide housed at E.P. Foster Library, Ventura, California.